The latent category of resilience and its relationship with the mental health and coping styles of medical students - Song, Jiang-Yan; Gao, Ya-Qin; Li, Hui-Ping; Gao, Jie; Li, Jia-Xin; Bi, Qing-quan; Li, Shu-Mei; Ye, Yun (Frontiers in Education, 2023)
Background Medical students suffer more pressure due to various reasons and their mental health problems get more attention. Resilience is a positive psychological perspective to explore the medical students’ mental health and coping style problems. This study focuses on the medical students in school and uses the method of latent category analysis (LCA) to analyze the classification characteristics of their resilience. Therefore, the study aims to help psychological educators in medical colleges to develop positive mental health education strategies for medical students. Objective To explore the potential categories of resilience of medical students and the relationship between these categories and mental health and coping style. Methods A total of 1,457 medical students from four medical colleges in Anhui Province were selected as the research subjects by a convenience sampling method. A general information questionnaire, the Connor-Davidson Resilience Scale (CD-RISC), Kessler 10 and the Simplified Coping Style Questionnaire (SCSQ) were used to investigate; SPSS 25.0 and Mplus 7 software were used for basic analysis and latent category exploration. Expected results The medical students were divided into three potential categories of mental resilience: the low resilience group, moderate resilience self-improvement group and high resilience tough group. The optimism dimension level of the three categories was low. There were statistically significant differences in the distribution of resilience among medical students, such as gender, source of students, and paternal and maternal education level. There were significant differences in the mental health, positive coping style and negative coping style scores among the three categories. Female medical students with low parental education levels have a lower level of resilience. Logistic regression analysis showed that a lower maternal education level was a risk factor for resilience level, and a high positive coping style score and gender were protective factors for resilience level. Discussion There are group differences in the resilience of medical students, which suggests that school health workers should formulate targeted intervention programs for different types of students to improve their resilience and mental health, and further more, this study reminds mental health workers in colleges and universities to pay more attention to the mental health status of female medical students whose parents are less educated.